Activation of the endothelin system in healthy and inflamed lungs: A mechanism for cardiovascular effects of air pollution - Thomson, Errol (University of Ottawa (Canada), 2007)
Circulating levels of the potent vasoconstrictor endothelin (ET) are increased after inhalation of urban pollutants. This effect could explain the association of air pollution and cardiovascular morbidity and mortality. However, the timing, source, and specific molecular basis of the increased endothelin release are not well defined. We hypothesized that inhalation of urban pollutants rapidly activates pulmonary endothelin system genes, resulting in increased production and spillover of the peptide into circulation. A time-course study confirmed rapid and transient increases of pulmonary preproET-1 and endothelin-converting enzyme-1 mRNA in rats exposed to particulate matter and ozone. Dose-response studies revealed that each pollutant individually activated endothelin system genes, consistent with the concomitant increase of the 21 amino acid peptide ET-1[1-21] and its precursor, bigET-1, in plasma. In contrast, pulmonary preproET-3 mRNA did not correlate with plasma ET-3 levels. Analyses in other organs revealed ozone-induced increases of endothelin gene expression in the brain, pituitary, and heart, substantiating the notion of extrapulmonary effects of pollutants. Surprisingly, co-exposure to particles and ozone increased pulmonary preproET-1 mRNA but not plasma ET-1[1-21] immediately after exposure. This coincided with an increase of matrix metalloproteinase-2, an enzyme that cleaves bigET-1 to ET-1 [1-32], suggesting that factors released during acute lung injury can modify circulating endothelin levels. To examine the effect of particle inhalation on existing lung pathology, we undertook microarray studies using SP-C/TNF-alpha mice with chronic lung inflammation and their wildtype littermates. Real-time PCR confirmed that inhalation of particles increased pulmonary preproET-1 and cytochrome p450 polypeptide 1 a1 mRNA, validating delivery of a biologically effective dose. Remarkably, microarray analyses failed to detect effects of particle exposure on pulmonary gene expression. Our data reinforce the notion that adverse health effects of acute exposure to urban particles may be dominated by physiological response cascades, with some transcriptional regulation such as activation of the endothelin pathway in target cells, rather than widespread changes in genes escaping homeostatic control. The rapid effects on a key vasoregulatory pathway in the lungs and brain provide a biological basis to explain the acute cardiovascular and cerebrovascular events that occur within hours of increased levels of air pollution.
Keywords: Health Sciences, Toxicology.; Chemistry, Biochemistry.; Biology, Physiology.